Intra-operative characterisation of subthalamic oscillations in Parkinson's disease. Issue 5 (May 2018) - Geng, Xinyi; Xu, Xin; Horn, Andreas; Li, Ningfei; Ling, Zhipei; Brown, Peter; Wang, Shouyan
Highlights: The 3-D visualized subthalamic area and the local field potential (LFP) oscillations were estimated intraoperatively. The resting and movement modulated oscillations had focal maxima in frequency bands. Movement related modulations showed differences in the scale and timing across frequency bands. Abstract: Objective: This study aims to use the activities recorded directly from the deep brain stimulation (DBS) electrode to address the focality and distinct nature of the local field potential (LFP) activities of different frequency. Methods: Pre-operative and intra-operative magnetic resonance imaging (MRI) were acquired from patients with Parkinson's disease (PD) who underwent DBS in the subthalamic nucleus and intra-operative LFP recording at rest and during cued movements. Images were reconstructed and 3-D visualized using Lead-DBS® toolbox to determine the coordinates of contact. The resting spectral power and movement-related power modulation of LFP oscillations were estimated. Results: Both subthalamic LFP activity recorded at rest and its modulation by movement had focal maxima in the alpha, beta and gamma bands. The spatial distribution of alpha band activity and its modulation was significantly different to that in the beta band. Moreover, there were significant differences in the scale and timing of movement related modulation across the frequency bands. Conclusion: Subthalamic LFP activities within specific frequency bands can be distinguished by spatial topography and pattern of movement related modulation. Significance: Assessment of the frequency, focality and pattern of movement related modulation of subthalamic LFPs reveals a heterogeneity of neural population activity in this region. This could potentially be leveraged to finesse intra-operative targeting and post-operative contact selection.